Production of bio-jet fuel range alkanes from catalytic deoxygenation of Jatropha fatty acids on a WOx/Pt/TiO2 catalyst. (1st March 2018) - Choi, Il-Ho; Lee, Jin-Suk; Kim, Chul-Ung; Kim, Tae-Wan; Lee, Kwan-Young; Hwang, Kyung-Ran
Graphical abstract: Highlights: A highly active and selective WOx/Pt/TiO2 catalyst for catalytic deoxygenation with no added hydrogen. W addition to Pt/TiO2 catalyst remarkably enhanced the degree of deoxygenation of free fatty acids. Intimate contact of W with Pt nanoparticles supported by TiO2 permits easier decarboxylation reaction. Abstract: Bio-jet fuel range alkanes were prepared by catalytic deoxygenation reaction of non-edible acid oils with no added hydrogen. A WOx[6]/Pt[1.6]/TiO2 was used for the deoxygenation of stearic acid and Jatropha fatty acid derived from Jatropha oil by hydrolysis. Tungsten addition to the Pt/TiO2 showed remarkably enhanced performance, a degree of deoxygenation of 86%, which is more than two times higher than that of the Pt/TiO2, even though the WOx/TiO2 had almost no activity for deoxygenation reaction. The enhanced Pt-related hydrogen uptake, measured by H2 -TPR, and XPS analysis showed the intimate contact of tungsten with Pt nanoparticles supported on TiO2 . This tight contact allows for easier CC cleavage over Pt nanoparticles and this is assisted by the strong bonding between tungsten and oxygen in the reactant, resulting in more C17 hydrocarbon production on the WOx/Pt/TiO2 .